PROMOTING ALGORITHMIC THINKING THROUGH UNPLUGGED PRIMARY SCIENCE ACTIVITY IN RURAL SCHOOLS - Tracy Mensan; Kamisah Osman; Nazatul Aini Abdul Majid (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
Algorithmic thinking, a method for solving problems through a step-by-step process that leads to a solution, is an essential component of computational thinking. Combining computational thinking and artificial intelligence (AI) in rural areas through unplugged activities provides an innovative approach to enhance science inquiry education. This article proposed the integration of algorithmic thinking and artificial intelligence (AI) within rural primary science education through hands-on, unplugged activities. Recognizing the challenges posed by limited digital access in these areas, the study introduces a model that encourages young learners to participate in STEM inquiries using practical, algorithm-oriented tasks that require little to no technology. This method promotes critical thinking, problem-solving skills, and scientific exploration by aligning with Piaget’s stages of cognitive development, allowing students to interact with materials and engage in practical scenarios. Furthermore, the research emphasizes how algorithmic thinking enhances logical reasoning and STEM literacy. By incorporating interactive games such as “Algorithm Walk” and “Science Sorting Relay,” the proposed model offers a contextually relevant and cost-effective approach to integrating computational thinking and fundamental AI concepts into primary education, effectively preparing students for future careers in science and technology. This would help in developing more customized, effective educational strategies and policies aimed at truly elevating meaningful educational experiences.